The planning fallacy put into context: Investigating the role of control in human time perception - Morrissey, DKC (2019)
People are prone to underestimate how long tasks will take them. This is a common phenomenon that has been named the planning fallacy (Kahneman & Tversky, 1977). This phenomenon can be observed in everyday life on relatively short time scales and also holds true for large-scale projects that involve forecasting for long time horizons. Kahneman and Lovallo (1993) suggested that one mechanism that could underlie the planning fallacy is the so-called optimism bias, a bias which has also been linked to heightened perceptions of control (Shepperd, Waters, Weinstein & Klein, 2015). This thesis was the first experimental investigation into the relationship between objective controllability of a task and future task completion time underestimations, as is characteristic of the planning fallacy. The experiments in this thesis investigated whether predictions of future task completion times would be shorter following controllable experimental tasks as compared to following uncontrollable experimental tasks. It was found that participants indeed made shorter future task completion time estimates following a controllable task. Furthermore, when compared to their actual completion times it was found that these estimates represented an underestimation. That such underestimations were not found for past completion time estimates, is in line with the inside-outside model of the planning fallacy (Kahneman & Tversky, 1977) and the Extended Inside-Outside Model of the planning fallacy proposed by Buehler, Griffin and Peetz (2010) and Buehler and Griffin (2015). The second variable that was investigated in its effect on future task completion time estimates was the subjective perception of control over a task. It was found that subjective control perceptions were not related to future task completion time estimates. This finding was also replicated by experiments involving real-life tasks. It had been predicted that people who perceive themselves as being more in control over completing the task in a timely manner would predict shorter task completion times. However, this prediction was not supported. Furthermore, individual-difference variables, such as depression, the desire for control and the intolerance of uncertainty, had been predicted to be associated with future task completion time estimations. However, no relationship was found. Taking the findings of all the experiments in this thesis together, it is proposed that it is the objective controllability of the task preceding the prediction that influences future task completion time predictions and not the subjective perception of controllability over the preceding or the future task. A new explanatory model of the planning fallacy is proposed, The Control Model of Future Time Prediction, in which the controllability of both the past task and the future task are taken into account to explain future task completion time predictions.